Soil improvement for tree stability volume 1 - Indrawan, I Gde Budi (2016)
This project report consists of three volumes. Volume I of this project report contains study of soil improvement for tree stability. Soil improvement for stability of trees is important for maintaining the sustainability of the “garden city” environment in Singapore. Trees are part of urban environment and provide numerous advantages to human life. However, uprooted trees can be dangerous since they may cause damage to properties (e.g., houses and vehicles) and infrastructures and may also cause injury or loss of life. The engineering properties of soil as a medium for tree growth also play an important role in tree stability. Finer-gained soils, such as top soil, have commonly been used for tree growing media. However, there have been several cases of tree failures associated with low soil strength occurring in Singapore. Therefore, in order to improve the soil strength for tree stability, top soil was mixed with granite chips at different percentages. Results of laboratory tests conducted showed that the hydraulic properties and shear strength of the top soils changed with the addition of granite chips. The air-entry value, y/a, residual matric suction, y/r, and residual volumetric water content, Or, of the soil mixtures decreased with the increase in the granite chip content. Beyond the air-entry value of the granite chip, the shape of SWCCs of the soil mixture of 80% granite chip and 20% top soil and the soil mixture of 50% granite chip and 50% top soil were controlled by the shape of SWCC of the top soil. The effective angle of internal friction, ¢', of the soil mixture increased by 25% (i.e., from 33° to 44°) with an addition of 50% granite chips and increased by 31% (i.e., from 33° to 48°) with an addition of 80% granite chips. The angle indicating the rate of increase in shear strength relative to the increase in matric suction, $ b, of the soil mixtures decreased with an increase in granite chip content. A field plot was developed where Rain trees (Samanea saman) were planted in insitu soil (IIF), top soil (TIF), 50GC-50TS, and 80GC-20TS. Statistical analyses of tree growth performance showed that the trees planted in the soil mixtures (i.e., 50GC-50TS and 80GC-20TS) grow as well as those planted in IIF and TIF, which are soils commonly used as tree growing media in Singapore. However, 80GC- 20TS was found to be the optimum mixture condition that gave the highest dry density. Field pull-out tests were conducted to assess the stability of the planted trees. The mean maximum pulling force of trees planted in 80GC-20TS was found to be higher than that of trees planted in TIF. There a trend of improvement in tree stability by mixing top soils with granite chips, although statistical analysis results show that the mean differences in the maximum pulling force and pulling energy were not statistically significant. A relatively strong correlation was indicated between the maximum pulling force and root plate volume, as well as root cross-sectional area (CSA) measured at the end of research. The large root CSA of 80GC-20TS suggested that the high density of 80GC-20TS caused the roots to grow bigger. The relatively longer and bigger roots of trees planted in 80GC-20TS caused the trees planted in 80GC-20TS to have maximum pulling forces that were higher than those planted in TIF.